SPECTROPHOTOMETRIC STANDARDS 8m-10m. Ш. THE EQUATORIAL ZONA FROM 12h TO 24h - Tereschenko, V.M. (Academic Scientific Journal of Computer Science, 2020)
This article is the third paper from cycle of notices, which devoted of the creation of spectrophotometric standards of in-termediate brightness. In paper the absolute energy distribution in visual region of spectra for 12 B-A-stars 8m-10m were present. The investigated stars-standards are located along the celestial equator in the range of right ascensions from 0h to 12h. Together with the stars from the second work of this cycle, they form a system of equatorial standards of intermediate brilliance. As a product of these two works, the total number of spectrophotometric standards of 8m-10m in the visible spectrum area has more than doubled. Equipment, observation methods, reductions and computations detailed described in our first and second papers. The distribution of energy was studied in the range of 340nm - 665nm, the spectral resolution of the data is 5nm, the relative standard error of the received data - from 2 to 6%. The reliability of the results is assessed by comparing the calculated and directly observed star magnitudes of the investigated stars in the UBV-system. For several stars, the distribution of energy in their spectrums, in addition to the observations, was calculated by photometric data. Differences between them in the ultraviolet region can reach 20-30% due to differences in the course of energy distribution curves in their spectrums, errors in spectral classification and determination of interstellar absorption.